Contribuição a industrialização do coco (Cocus nucifera, L.) leite de coco e coco ralado - Teixeira, Evânia Altina Mendonça (1986)
Coconut milk and desiccated coconut are () products derived from the coconut (Cocus nucifera, L.) and since they are widely accepted in Brazilian market, they are produced industrially in various industrial complexes in northearstern Brazil [...]